Hereditary hemochromatosis: what have we learnt from population studies - Olynyk, John K. (Henry Stewart Talks, 2011)
Hereditary haemochromatosis, Iron metabolism, Definition, Diagnosis, Clinical and biochemical penetrance, Genetic and environmental modifiers, Diagnostic algorithm, Update talk: Treatment improves symptoms, Update talk: C282Y homozygotes & elevated ferritin, Update talk: New markers for HH detection, Update talk: Use of MCV and MCH, Update talk: Arthritis risk in HH, Update talk: Detection of hepatic fibrosis, Update talk: Risk of liver cancer
Updated at 2021/05/31